Expression and Cellular Distribution of P-Glycoprotein and Breast Cancer Resistance Protein in Amyotrophic Lateral Sclerosis Patients. Issue 3 (27th December 2019) - van Vliet, Erwin A; Iyer, Anand M; Mesarosova, Lucia; Çolakoglu, Hilal; Anink, Jasper J; van Tellingen, Olaf; Maragakis, Nicholas J; Shefner, Jeremy; Bunt, Ton; Aronica, Eleonora
Abstract: For amyotrophic lateral sclerosis (ALS), achieving and maintaining effective drug levels in the brain is challenging due to the activity of ATP-binding cassette (ABC) transporters which efflux drugs that affect drug exposure and response in the brain. We investigated the expression and cellular distribution of the ABC transporters P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) using immunohistochemistry in spinal cord (SC), motor cortex, and cerebellum from a large cohort of genetically well characterized ALS patients (n = 25) and controls (n = 14). The ALS group included 17 sporadic (sALS) and 8 familial (fALS) patients. Strong P-gp expression was observed in endothelial cells in both control and ALS specimens. Immunohistochemical analysis showed higher P-gp expression in reactive astroglial cells in both gray (ventral horn) and white matter of the SC, as well as in the motor cortex of all ALS patients, as compared with controls. BCRP expression was higher in glia in the SC and in blood vessels and glia in the motor cortex of ALS patients, as compared with controls. P-gp and BCRP immunoreactivity did not differ between sALS and fALS cases. The upregulation of both ABC transporters in the brain may explain multidrug resistance in ALS patients and has implications for the use of both approved and experimental therapeutics.